Intentions and Behavior of Using Gopay in Accounting Students - Trisna Ayu Aprilia; Gede Juliarsa (E-Jurnal Akuntansi, 2025)
This research is aimed at understanding the intention and behavior of using Gopay using the UTAUT3 model framework. This research was carried out on accounting students at the Faculty of Economics and Business, Udayana University, who used Gopay. Purposive sampling is used as a sampling technique. Data was collected using an online questionnaire method. A total of 186 people were sampled. SEM-PLS was used as a data analysis technique method in this research. The findings of this research show that price value, habits, and personal innovation have a significant positive influence on usage intention. Facilitating conditions, personal innovation and intention to use were also found to have a positive and significant effect on Gopay usage behavior.